Structured Problem Solving: German Methodology from a Comparative Perspective - Lutz-Christian Wolff (Legal Education Review)
In its review of the Federal civil justice system, the Australian Law Reform Commission recommended that, “in order to enhance appreciation of ethical standards and professional responsibility, law students should be encouraged and provided opportunity to undertake pro bono work as part of their academic or practical legal training requirements.” This recommendation was endorsed by the National Pro Bono Task Force in its report delivered to the Federal Attorney General in June 2001. To achieve this goal, the Task Force recommended that all law students should be provided with: • opportunities for internships/outreach programs with a pro bono focus; • opportunities to undertake clinical experience; • clinical components within the academic curriculum; • stand-alone electives such as “Public Interest Advocacy”; and • opportunities for reflection upon and critical analysis of ethical matters (including pro bono) in the classroom.